Frequency of Pre-Eclampsia in High-Risk Pregnant Women Treated with Low Dose Aspirin (LDA) Presenting in Tertiary Care Hospital - Nilofar Mustafa, Gulzaib Anwar, Rehana Kanwal, Pakeeza Aslam, Qurutulain Mushtaq, Shazia Tufail, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of pre-eclampsia among high-risk pregnant women treated with low dose aspirin (LDA) presenting in a tertiary care hospital. Study design: Descriptive study Duration of study: Six months from 20-02-2018 to 19-08-2018. Setting: Study was conducted in OPD of Obstetrics and Gynaecology Department, Combined Military Hospital, Lahore National University of Medical Sciences NUMS Material and methods: A total of 175 patients were included in the study. Pregnant females diagnosed as high risk were treated with low dose aspirin (75 mg) daily started at 12 to 16 weeks of gestation till the end of pregnancy. 24 hours urine protein test was done for patients with B.P. >140/90mmHg after 20 weeks of gestation and if at least 300mg protein was present in 24 hours urine then patient was labeled as pre-eclamptic. Results: Patients ranged between 20-35 years of age with mean age of 25.9±3.6 years. Mean gestational age was 14.4±1.1 weeks and mean BMI was 27.3±4.3 kg/m2. Pre-eclampsia developed in 27 patients (15.4%). Obesity found in 53 patients (30.3%). There were 27 (15.4%) primigravida and 148 (84.6%) multigravida patients. Conclusion: In conclusion, low dose aspirin is effective in prevention of preeclampsia in high-risk patients. Indications for aspirin in primary prevention are a matter of debate, but recent publications suggest a strategy based on first-trimester screening of preeclampsia (with clinical parameters, biomarkers and uterine artery Doppler measurements) and aspirin administration to high-risk patients. Keywords: Aspirin, High risk pregnancy, Pre-eclampsia